Metabolic Syndrome in the Spectrum of Hair Graying - Ahmed A. Kawen; Hayder R. Al-Hamamy; Zaid F. Abdullah (The Medical Journal of Basrah University, 2017)
Background: Hair graying is an aging sign that was found to be associated with several systemic diseases like ischemic heart disease, osteopenia, and autoimmune diseases. Metabolic syndrome was applied to the clustering of risk factors that often associate with increased risk for atherosclerotic cardiovascular disease. Aim of Study: Our work aimed to test retrospectively the association between onset of hair graying and risk of metabolic syndrome. Patients & Methods: Four hundred and eighty one gray hair individuals, with no history of any type of atherosclerotic disease, participated in the study. The participants were divided into two groups according to the presence or absence of criteria of metabolic syndrome into control and metabolic syndrome groups, and each individual in both groups was asked about the decade (2nd-6th) when he/she firstly noticed that he/she had a gray hair. A comparison was made regarding the age of onset of graying between the two groups. Results: There was a significant difference in decades between individuals with metabolic syndrome and the control group and was found in the 4th and 5th decade of life (P =0.045 & 0.024 respectively) while the difference was not significant in the 2nd, 3rd and 6th decades of life. The mean age of onset of hair graying in metabolic syndrome was 36.207 ± 8.30 year and the control group was 38.434 ±8.31 year, there is also a significant difference between the two groups (P value=0.003). Conclusion: patients with metabolic syndrome have an earlier age of onset of gray hair.